Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.molmed.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pathogens versus Autophagy: Implications for Therapeutic Interventions

Abstract: Research in recent years has focused significantly on the role of selective macroautophagy in targeting intracellular pathogens for lysosomal degradation, a process termed xenophagy. In this review we evaluate the proposed roles for xenophagy in controlling bacterial infection, highlighting the concept that successful pathogens have evolved ways to subvert or exploit this defense, minimizing the actual effectiveness of xenophagy in innate immunity. Instead, studies in animal models have revealed that autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 144 publications
2
120
0
Order By: Relevance
“…Of these, S. flexneri, the most closely related to Salmonella, also replicates within the cytosol of intestinal epithelial cells. Both rely on T3SS-mediated pore formation to escape from the vacuole, but this is a double-edged sword since it is also a potent activator of host cytosolic defenses (Kimmey and Stallings, 2016). Specifically, bacteria are subject to a variation of autophagy known as xenophagy, an evolutionarily conserved mechanism, which controls Salmonella replication (Birmingham et al, 2006;Jia et al, 2009;Benjamin et al, 2013;Conway et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, S. flexneri, the most closely related to Salmonella, also replicates within the cytosol of intestinal epithelial cells. Both rely on T3SS-mediated pore formation to escape from the vacuole, but this is a double-edged sword since it is also a potent activator of host cytosolic defenses (Kimmey and Stallings, 2016). Specifically, bacteria are subject to a variation of autophagy known as xenophagy, an evolutionarily conserved mechanism, which controls Salmonella replication (Birmingham et al, 2006;Jia et al, 2009;Benjamin et al, 2013;Conway et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore conclude that the observed autophagic processes that promote intracellular replication of Y. enterocolitica require induction of canonical macroautophagy pathways distinct from LAP. Huang & Brumell, 2014, Kimmey & Stallings, 2016. The mechanisms, by which these bacteria subvert or hijack autophagy pathways are, however, mostly unclear (Huang & Brumell, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…consequence evolved mechanisms to evade or modulate autophagyrelated pathways for their own benefit to establish disease (Huang & Brumell, 2014;Kimmey & Stallings, 2016;Kohler & Roy, 2017;Mostowy & Cossart, 2012).…”
mentioning
confidence: 99%
“…Importantly, results from Yoshikawa et al (2009) suggested that the ability of ActA to prevent recognition of L. monocytogenes by autophagy is independent of actin polymerization and actin-based motility. Although the conclusions of Yoshikawa et al (2009) dominate the current literature (Choy and Roy, 2013; Gong et al , 2012; Huang and Brumell, 2014; Kimmey and Stallings, 2016; Mostowy, 2013; Mostowy and Shenoy, 2015; Pareja and Colombo, 2013; Welch and Way, 2013), it is still unclear if actin polymerization and actin-based motility play a role in the avoidance of L. monocytogenes from autophagy during macrophage infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the conclusions of Yoshikawa et al (2009) dominate the current literature (Choy & Roy, 2013;Gong, Devenish, & Prescott, 2012;Huang & Brumell, 2014;Kimmey & Stallings, 2016;Mostowy, 2013;Mostowy & Shenoy, 2015;Pareja & Colombo, 2013;Welch & Way, 2013), it is still unclear if actin polymerisation and actin-based motility play a role in the avoidance of L. monocytogenes from autophagy during macrophage infection.…”
mentioning
confidence: 99%